Clinical significance of detection of mononuclear phagocyte subsets in blood and bronchoalveolar lavage fluid (BALF) in pulmonary sarcoidosis - Qiaozhen, Hong; Jifei, Zhang; Lingrong, He; Qiuming, Yu; Hongjuan, Yu; Qiaozhen, Hong (Cellular and Molecular Biology, 2022)
This study aimed to investigate the clinical significance of the detection of mononuclear phagocytes subsets in pulmonary sarcoidosis blood and bronchoalveolar lavage fluid (BALF). For this purpose, a total of 52 patients with pulmonary sarcoidosis were selected as the study group, 52 healthy people served as the “NC Group a” (peripheral blood mononuclear cell control group), 47 patients with chronic cough and no pulmonary sarcoidosis who underwent bronchoscopy were used as “control group b” (alveolar lavage fluid macrophage control group). Fasting peripheral blood and BALF were collected, and flow cytometry was used to detect monocytes and macrophage subpopulations. The monocytes and macrophage subpopulations of the study group were compared before and after treatment. The results showed that the proportion of CD14++CD16- subgroup of patients with pulmonary sarcoidosis was lower than that of healthy people (74.21±4.10% vs 84.32±4.76%); The proportion of CD14++CD16+ subgroups of patients with pulmonary sarcoidosis was higher than that of healthy people (7.42±4.08% vs 3.95±1.94%); The proportion of CD14+CD16++ subgroups of patients with pulmonary sarcoidosis was higher than that of healthy people in the control group, but the difference was not significant. After 2 months of treatment, the proportion of CD14++CD16- subgroups in peripheral blood mononuclear cells increased, and the proportion of CD14++CD16+ subgroups decreased. The proportion of M1 in patients with pulmonary sarcoidosis was lower than that in patients with non-pulmonary nodules (24.32±11.36% vs 47.03±13.86%); the proportion of M2 in patients with pulmonary sarcoidosis was higher than the proportion of M2 in patients with non-pulmonary nodules (75.40±10.23% vs 52.53±12.01%). After treatment, the proportion of M1 of BALF macrophages in patients with pulmonary sarcoidosis was increased (P<0.05), and the proportion of M2 was reduced (P<0.05). In general, detection of changes in peripheral blood mononuclear cell subpopulations and BALF macrophage subpopulations in patients with pulmonary sarcoidosis has certain clinical significance for the treatment.